Er:YAG laser irradiation surface effect of set bioceramic endodontic sealer – in vitro SEM study - V. Stefanova; K. Zhekov (Frontiers in Bioengineering and Biotechnology)
IntroductionRecent developments in endodontics have led to increased interest in utilizing different methods for the removal of bioceramic endodontic sealers. The Er:YAG laser’s specific wavelength and energy delivery, we foresee its potential in laser-assisted removal of bioceramic sealers like BioRoot RCS.AimThe primary aim is to examine the influence of Er:YAG laser irradiation on set BioRoot RCS and to discern and compare the effects on the sealer of two different time durations and two distinct laser settings.Materials and MethodsSpecimens of BioRoot RCS (n = 20), each 10 mm in diameter and 3 mm thickness, were prepared according to manufacturer guidelines and set for 48 h at 37°C and 100% relative humidity. The “LiteTouch” Er:YAG laser system was applied with two different settings: 300 mJ, 5.10 W, 17 Hz, and water spray rate of 5, irradiation time 20 s for Group A (n = 5) and 40 s for Group B (n = 5). Settings of 250 mJ, 5.00 W, 20 Hz, with the same spray rate were used for 20 s irradiation for Group C (n = 5) and 40 s for Group D (n = 5). The laser sapphire tips employed were with dimensions D-1.3 mm and L-19 mm. Only half of each specimen underwent laser treatment, ensuring a controlled and comparative analysis of surface alterations and material removal, assessed using scanning electron microscopy on four different magnifications (x1,000; x2,000; x5,000 and x10,000).ResultsAll irradiated specimens demonstrated significant macroscopic and microscopic surface changes. We selected and compared scenograms of non-laser treated surfaces and laser treated surfaces of all experimental groups on the four magnifications. For Group A and Group B a greater effect on the material surface was observed in comparison with group C and Group D. Group B and Group D presented more substantial surface alterations compared to group A and Group C respectively.ConclusionEr: YAG laser irradiation effectively alters the surface of the set BioRoot RCS. Longer irradiation time and bigger overall energy settings show superior changes. This pioneer in vitro investigation shows the possible use of lasers for bioceramic sealer removal in order to impact retreatment endodontic procedures.